2016
DOI: 10.5194/hess-20-625-2016
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Testing an improved index for analysing storm discharge–concentration hysteresis

Abstract: Abstract. Analysis of hydrochemical behaviour during storm events can provide new insights into the process controls on nutrient transport in catchments. The examination of storm behaviours using hysteresis analysis has increased in recent years, partly due to the increased availability of high temporal resolution data sets for discharge and water quality parameters. A number of these analyses involve the use of an index to describe the characteristics of a hysteresis loop in order to compare storm behaviours … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 28 publications
3
142
1
Order By: Relevance
“…This variability was quantified through the application of the HI, which enables robust comparison of data between storm events of different magnitudes [Lloyd et al, 2016a]. Our modeling results suggested that observed hysteresis patterns were driven by a combination of the hydroclimatological conditions of each particular storm event, coupled with the antecedent hydroclimatological conditions in the period leading up to that event [Darwiche-Criado et al, 2015].…”
Section: Identification Of Nutrient Source Zone Activation Under Contmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability was quantified through the application of the HI, which enables robust comparison of data between storm events of different magnitudes [Lloyd et al, 2016a]. Our modeling results suggested that observed hysteresis patterns were driven by a combination of the hydroclimatological conditions of each particular storm event, coupled with the antecedent hydroclimatological conditions in the period leading up to that event [Darwiche-Criado et al, 2015].…”
Section: Identification Of Nutrient Source Zone Activation Under Contmentioning
confidence: 99%
“…Predictor variables were transformed where necessary and standardized to improve the interpretability of regression coefficients, i.e., effect sizes [Schielzeth, 2010], and the robustness of the statistics. We then fitted all possible subset models of the global model and ranked them using AIC values [Bowes et al, 2005;Chen et al, 2012;Outram et al, 2014;Lloyd et al, 2016b] To better understand the processes controlling nutrient-specific export patterns observed at the catchment outlet (see hypothesis 3), NO 3 -N and DOC were characterized as hysteresis indices (HI) for each storm event using methods developed by Lloyd et al [2016a]. The HI for each storm quantifies the "fatness" and direction of the hysteresis loop, whereby clockwise hysteresis behavior is represented by positive HI values and anti clockwise behavior by negative values.…”
Section: Hydroclimatological Drivers Of No 3 -N and Doc Export Duringmentioning
confidence: 99%
“…Other studies have used index‐based approaches to assess solute (Butturini, Alvarez, Bernal, Vazquez, & Sabater, ; Lloyd, Freer, Johnes, & Collins, ; M. C. H. Vaughan, Bowden, et al, ) and particulate (Aich, Zimmermann, & Elsenbeer, ; Langlois, Johnson, & Mehuys, ; Lawler, Petts, Foster, & Harper, ; Sherriff et al, ) hysteresis during events. Various quantitative hysteresis indices (HIs) exist that variously compare the C‐Q regression relationships on the rising and falling hydrograph limbs (Langlois et al, ), the ratio of constituent concentrations on the rising and falling limbs (Lawler et al, ), and the size of hysteresis loops (Aich et al, ; Lloyd et al, ; M. C. H. Vaughan, Bowden, et al, ). The HI proposed by Lloyd et al () and modified by M. C. H. Vaughan, Bowden, et al () uses normalized discharge and concentrations to quantify differences on the rising and falling hydrograph limbs.…”
Section: Introductionmentioning
confidence: 99%
“…As is evident from the positive hysteresis observed in this study (Figure 6), there is a dilution of nitrate on the rising limb of each storm event within the Greensboro watershed. Several researches have reported similar response for agricultural watersheds [43][44][45]. Figure 8 shows boxplots of storm nitrate concentration at different flow percentiles for all monitored storm events and demonstrates that median storm nitrate concentration decreases with increases in flow.…”
Section: Effect Of Hysteresis On Nitrate Load Estimationmentioning
confidence: 56%